2020
DOI: 10.1111/1750-3841.15456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma irradiation on physico‐mechanical and structural properties of active Farsi gum‐CMC films containingZiziphora clinopodioidesessential oil and lignocellulose nanofibers for meat packaging

Abstract: The objective of this study was to examine the effect of gamma irradiation (0, 2.5, and 5 kGy) on physico-mechanical and structural characteristics of films based on Farsi gum-carboxymethyl cellulose supplemented with Ziziphora clinopodioides essential oil (ZEO; 0%, 1%, and 2%) and lignocellulose nanofibers (LCNF; 0%, 1%, and 2%), and their application on fresh minced beef meat's shelf-life during refrigerated temperature (4 ± 1°C) for 16 days. Gamma irradiation under the 60 Co source at 2.5 and 5 kGy doses di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…They concluded incorporation of ZG into polyvinyl alcohol leads to remarkable alteration in the intensity and position of the peaks, which demonstrates appropriate mixing between the two polymers (Razmjoo et al, 2021). Bahari et al (2020) assess the impact of gamma irradiation on physico‐mechanical features of farsi gum‐CMC films containing Ziziphora clinopodioides essential oil and lignocellulose nanofibers for meat packaging (Bahari et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded incorporation of ZG into polyvinyl alcohol leads to remarkable alteration in the intensity and position of the peaks, which demonstrates appropriate mixing between the two polymers (Razmjoo et al, 2021). Bahari et al (2020) assess the impact of gamma irradiation on physico‐mechanical features of farsi gum‐CMC films containing Ziziphora clinopodioides essential oil and lignocellulose nanofibers for meat packaging (Bahari et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the broad characteristic peak at 20.61°for FG indicated a semi-crystalline microstructure. 74 The XRD pattern of Alg showed two characteristic broad diffraction peaks at 14.05°and 22.01°, indicating the semicrystalline structure of Alg. 75 The XRD diffraction peak of FG shifted from 20.61°to 21.16°, 21.56°, 21.56°, and 22.56°in FG-Fe, Gel, Gel-BiH, and Gel-BiH-Alla hydrogels, respectively, indicating the formation of metal-coordination bonds.…”
Section: Preparation and Characterization Of Hydrogelsmentioning
confidence: 96%
“…For example, CS films incorporated with Cinnamodendron dinisii Schwanke essential oil-loaded zein have been reported to successfully stabilize the deterioration reactions in ground beef 94 . Farsi gum-CMC films containing Ziziphora clinopodioides essential oil and lignocellulose nanofibers have also been exploited as packaging materials to extend the shelf life of fresh minced beef meat 95 . Although these packaging materials are not self-healable films and coatings, their success in packaging food products other than vegetables and fruits implicates the worth of exploiting the packaging performance of self-healable materials beyond mere fruit and vegetable preservation.…”
Section: Opportunities and Challenges For Practical Applicationsmentioning
confidence: 99%